Corporate Social Responsibility Disclosure and Its Effect on Firm Risk: An Empirical Research on Vietnamese Firms - Cao Thi Mien Thuy (MDPI AG, 2021)
The purpose of the study was to gather empirical evidence on the influence of corporate social responsibility (CSR) disclosure on firm risk of Vietnam’s publicly listed companies. We used adjusted OLS estimation and regression analysis with adjusted panel data for heteroskedasticity and/or autocorrelation to analyze the correlation using data from 225 listed companies on Vietnam’s stock market from 2014 to 2019. The study’s sample period is relatively recent in the emerging market, especially considering regulatory differences and the availability of voluntary disclosure requirements. The findings of research on the relationship between CSR and corporate risk are mixed, particularly in developing markets. Research findings reveal a negative and significant association between CSR and firm risk, implying that stronger CSR performance lowers a company’s risk. This aims to strengthen a research perspective of this connection in emerging countries. Following that, we discuss some policy implications for listed firms and regulators in CSR disclosure.